Breakthrough COVID-19 infections, Hospitalization, and Mortality after Two CoronaVac shots at Thailand CVC - Sunan, Krittiyaporn; Pongpirul, Krit; Rattananupong, Thanapoom; Phutrakool, Phanupong; Suphannaphong, Mingkwan (Journal of The Department of Medical Services, 2024)
Background: Vaccination against COVID-19 plays a pivotal in combating the pandemic. in Thailand, large-scale population-based studies are limited. The Central Vaccination Center Thailand (CVC) has a vaccination record system linked to the national database, enabling a comprehensive study of vaccine efficacy. Objectives: To determine the incidence of COVID-19 infections, hospitalization, and mortality among individuals who received two doses of the CoronaVac (SV) vaccine. Additionally, to study the time to infections, hospitalization, and mortality after the first and second doses. Methods: A retrospective study was conducted from June to September 2021, involving 145,417 individuals who received the CoronaVac vaccine, totaling 291,415 doses. Results: We found 3,818 cases of COVID-19 infections (2.63%), 2,352 hospitalizations (1.62%), mostly mild (asymptomatic), and 3 deaths (<0.01%). After the second dose, there were 3,325 infections (2.31%), with an incidence rate of 0.025 (95% CI 0.0241, 0.0258) per 1,000 person-days; 2,186 hospitalizations (1.51%), with an incidence rate of 0.0163 (95% CI 0.0156, 0.0170) per 1,000 person-days; and 3 deaths, with an incidence rate of 0.0222 (95% CI 0.0072, 0.0688) per 1,000 person-days. Conclusion: The vaccine recipients were primarily Thai service provider such as public transport workers, postman, and courier, vaccinated during a period of high incidence and limited vaccine availability. The study indicates that a two-dose regimen of CoronaVac, administered as recommended to boost immunity, can reduce the incidence of infection, hospitalization, and mortality, thereby reinforcing the healthcare system.